Social stability risk assessment: status, trends and prospects —a case of land acquisition and resettlement in the hydropower sector. Issue 5 (3rd September 2021) - Peng, Shengping; Shi, Guoqing; Zhang, Ruilian
ABSTRACT: Social Impact Assessment (SIA) is widely used in the field of international evaluation, but its application in China has been limited. Based on the dual requirements of developing the economy and maintaining stability, social stability risk assessment (SSRA) systems have come into being in China at a historic moment. Starting from the similarities and differences between SIA and SSRA, this paper reviews the influencing factors, sources, evaluation methods, existing problems and suggestions of SSRA in major decision-making, policy, reform and construction projects. On this basis, considering Wudongde hydropower station as an example, the social stability risk of land acquisition and resettlement (LAR) is assessed by using fuzzy comprehensive evaluation (FCE) methods. The research shows that relying solely on SIA or SSRA makes it difficult to meet the social risk management requirements of major matters. SIA should be identified as a necessary link, and SSRA content should be embedded in SIA to achieve effective integration of the two.